Anomalous third part of axillary artery- anatomical, embryological and clinical relevance - Satyanarayana, N; Ranjit, G; Sunitha, P; Nitin, V; Praveen, G; Kumar, DA; Devi, PS (Journal of College of Medical Sciences-Nepal, 2012)
DOI: http://dx.doi.org/10.3126/jcmsn.v7i3.6711 Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-3, 43-47